The turbocharged wide anterolateral thigh perforator flap to reconstruct massive soft tissue defects in traumatized lower extremities: A case series - Jeong, Seong-Ho; Koo, Do-Yoon; Moon, Kyung-Chul; Dhong, Eun-Sang; Han, Seung-Kyu (Frontiers in Surgery, 2022)
Background: Extensive traumatic soft tissue defects in the lower extremities typically require perfect coverage of exposed bone because inadequate coverage, such as partial flap loss, may result in bony infection and ultimately lead to limb salvage failure. To achieve complete coverage of these defects, we used the wide anterolateral thigh perforator flap in which the turbocharging procedure augments the blood flow. Herein, we describe our turbocharging technique and discuss its effectiveness. Methods: From January 2014 to December 2020, the turbocharged wide ALTP free flaps were used to treat 13 patients with massive traumatic soft tissue defects in the lower extremities, ranging in size from 22×10 cm2 (220 cm2) to 21×17 cm2 (357 cm2) (mean, 270 cm2). All ALTP flaps were supplied by perforators from both the transverse branch of the lateral circumflex artery (TB-LCFA) and descending branch of the lateral circumflex artery (DB-LCFA) simultaneously. The turbocharging procedure by connecting the TB-LCFA to a side branch of the DB-LCFA was carried out in all these flaps. A retrospective review of medical records for each patient was performed. Results: The size of the transferred ALTP flap ranged from 23×12 cm2 (276 cm2) to 23×19 (437 cm2) (mean, 331 cm2). The total number of perforators included in the flaps was three on average. All ALTP flaps survived completely without partial necrosis. The postoperative course was uneventful except for two cases with minor complications, including hematoma and partial necrosis of the recipient's skin. Conclusion: Free transfer of the turbocharged wide ALTP flap can be a reliable and effective reconstructive method to obtain perfect coverage of extensive traumatic soft tissue defects in the lower extremities and achieve successful limb salvage.